Obstructive Sleep Apnea–Hypopnea Syndrome and Nonalcoholic Fatty Liver Disease: Emerging Evidence and Mechanisms - Musso, Giovanni; Olivetti, Carla; Cassader, Maurizio; Gambino, Roberto (Seminars in Liver Disease, 2012)
Obstructive sleep apnea syndrome (OSAS) and nonalcoholic fatty liver disease (NAFLD) are common conditions, frequently encountered in patients with metabolic disorders. OSAS has been associated with an increased risk of cardiovascular and metabolic complications. It has been recently suggested that the chronic intermittent hypoxia of OSAS may also affect the presence and severity of NAFLD. We will critically review experimental and human evidence connecting OSAS to NAFLD pathogenesis, trying to dissect the effect of intermittent hypoxia from that of obesity and associated comorbidities, and examine molecular mechanisms connecting OSAS to liver and metabolic disease in NAFLD, including hypoxia inducible factor (HIF), nuclear factor-kappa B, unfolded protein response, hypoxic adipose tissue inflammation, and their therapeutic potential for NAFLD and its complications, including cirrhosis and hepatocellular carcinoma. Finally, we will provide suggestions for the management of NAFLD patients with suspected OSAS and recommendations for future research.
Keywords: Sleep apnea; chronic intermittent hypoxia; hypoxia inducible factor; fatty liver